Coordinating invasive plant management among conservation and rural stakeholders. (February 2019) - Graham, Sonia
Highlights: In south-west Alberta invasive plant management (IPM) efforts are widespread. Individuals and institutions engage in participatory, linked and collaborative IPM. Coordinated IPM is needed to achieve a functional polycentric governance system. Abstract: Collective action among conservation and rural land managers is required to protect natural and rural ecosystems from the spread of invasive plants. Achieving such tenure-blind collective action is a considerable policy challenge and social research on this topic is in its infancy, is rural-focused and rarely addresses multiple species concurrently. This study explores the nature and extent of collective action among conservation and rural stakeholders managing multiple invasive plant species in south-west Alberta, Canada. Thirty telephone interviews were conducted with staff of national and provincial parks, non-government organisations and government agencies, as well as ranchers and consultants operating within the Oldman Watershed. The results showed three key types of collective action—participatory, linked and collaborative—occurring across the landscape. Collaborative invasive plant management (IPM) was the most likely to bring rural and conservation land managers together to address multiple species but was highly resource intensive and confined to public lands. A polycentric system of governance may enable landscape-wide IPM to be achieved if it can link existing collaborative efforts as well as establish and maintain new relationships among rural and conservation stakeholders. Organisations that encompass multiple land uses, such as watershed councils and municipal districts, may be best placed to bring diverse stakeholders together to develop a shared plan, facilitate social learning and demonstrate on-ground action at multiple scales across land uses.